Analysis of genetic relationship among Indonesian native chicken breeds based on 335 D-loop sequences - Sulandari, Sri; Arifin Zein, M. Syamsul; Sartika, Tike (Indonesian Animal Sciences Society, 2008)
The Mitochondrial DNA (mtDNA) D-loop segment was PCR amplified and subsequently sequenced for a total of 335 individuals from Indonesian native chicken. The individuals were drawn from sixteen populations of native chicken and three individuals of green jungle fowls (Gallus varius). Indonesian native chicken populations were: Pelung Sembawa, PL (n = 18), Pelung Cianjur, PLC (n = 29) and Arab Silver, ARS (n=30), Cemani, CM (n = 32), Gaok, GA (n = 7), Kedu Hitam, KDH (n = 11), Wareng, T & TW (n = 10), Cemani, CMP (n = 2), Kedu, KD (n=26), Kedu Putih, KDP (n = 15), Sentul Jatiwangi, STJ (n = 27), Ayam Kate, KT (n = 29), Ayam Sentul, STC (n = 15), Arab Golden, ARG (n = 26), Ayam Merawang, MR (n = 28), Kedu Putih Jatiwangi, KDPJ (n=6) and Kapas, KPS (n = 21). Green jungle fowls were: two individuals from Flores island (FL5 and FL57) and one individual (BD42) from Sumbawa island. The sequences of the first 530 nucleotides were used for analysis. Eighty two haplotypes were identified from 78 polymorphic sites for the 335 individuals. Seventy nine haplotypes were identified in native chicken from 57 polymorphic sites while three were of jungle fowls. Phylogenetic analysis indicates that Indonesian native chicken can be grouped into five clades (Clade I, II, IIIc, IIId and IV) of the previously identified seven clades (Clade I, II, IIIa, IIIb, IIIc, IIId and IV) in Asian domestic chicken. Haplotypes CM10 and CM32 fall to a different category while STC12 is also on its own. Interestingly STC12 clusters together with Gallus gallus gallus (GenBank accession No. SULANDARI et al. Analysis of genetic relationship among Indonesian native chicken breeds based on 335 D-loop sequences 296 AB007720). When CM10 (same as CM14), CM32 and STC12 were removed, 77 haplotypes of domestic chicken were identified from 53 polymorphic sites. All the green jungle fowls are clustered to one clade of their own. The clades of domestic chicken are: Clade I which has three haplotypes, Clade II has 52 haplotypes, Clade IIIc has one haplotype (represented by ARS30), Clade IIId has nine haplotypes while Clade IV has eleven haplotypes. The phylogenetic relationship between chicken populations has no link to the geographic locations. Analysis of molecular variance showed that the genetic variation within populations was 67.42% while 32.58% accounted for the genetic differentiation between populations. Key Words: Native Chiken, Green Jungle Fowls, D-Loop DNA Mitochondria, HV-1, Clade, Haplotype, Phylogenetic, Genetic Variation